Permeability Prediction By Classical and Flow Zone Indictor (FZI) Methods for an Iraqi Gas Field - Al-Qattan, Waffa Mustafa; Al Mohammed, Ahmed Habeeb (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
The permeability is the most important parameter that indicates how efficient the reservoir fluids flow through the rock pores to the wellbore. Well-log evaluation and core measurements techniques are typically used to estimate it. In this paper, the permeability has been predicted by using classical and Flow zone indicator methods. A comparison between the two methods shows the superiority of the FZI method correlations, these correlations can be used to estimate permeability in un-cored wells with a good approximation.